Prevalence, Vaccination Coverage, and Occupational Risk Factors for Hepatitis B and C Infections among Laboratory Health Workers at the Central Pediatric Teaching Hospital in Baghdad, Iraq - Abed Al-Haboobi, Sahar Hussein; Abdulhussein, Hassan Muslem; Mohammed, Yaser Raouf; Al-Rudaini, Riyadh Shiltagh (Journal of Neonatal Surgery, 2025)
Background: Hepatitis B and C infections represent critical occupational hazards for healthcare personnel, particularly among laboratory workers. Although HBV is preventable with vaccination, uptake remains inadequate in many low- and middle-income settings, while the absence of Hepatitis C virus (HCV) vaccine further complicates prevention efforts. This study aimed to determine the prevalence of Hepatitis B virus (HBV) and HCV among laboratory staff in Baghdad, assess vaccination coverage, and identify occupational risk factors to inform future safety protocols and policy reforms. Methods: This study conducted as a five-year retrospective cohort study at the Central Pediatric Teaching Hospital in Baghdad (January 2019–December 2024), data were collected from 242 laboratory workers (93.1% response rate) via medical record reviews and structured questionnaires. Information regarding demographics, vaccination history, occupational exposures, bloodborne pathogen awareness, and personal medical background was compiled. Statistical analyses using SPSS, including descriptive and bivariate methods, were performed to identify factors associated with HBV and HCV infections. Results: Among the 243 workers evaluated, most were female (83.1%) with a mean age of 32 years, and 81.5% were laboratory technicians; 64.6% reported direct patient contact. While 87.7% were knowledgeable about hepatitis transmission, 9.1% had inadequate training. Hepatitis B vaccination was reported by 73.3% of workers, but only 39.5% completed the full three-dose regimen, and merely 28.1% demonstrated serological immunity. Of 82 individuals reporting needlestick injuries, only 36.6% received post-exposure prophylaxis. Infection rates among participants who underwent serological testing were 2% for HBV and 9.4% for HCV. All HBV cases were among unvaccinated workers, and needlestick injuries were significantly linked to HBV infection (p = 0.012). Conclusions: The study reveals gaps in HBV/HCV vaccination, immunity testing, and safety protocols among lab workers, stressing the need for mandatory vaccination, serological monitoring, and enhanced training to reduce infection risks.